Highly efficient hydrogen evolution electrocatalysts based on coupled molybdenum phosphide and reduced graphene oxide derived from MOFs. Issue 93 (9th November 2017) - Li, Ji-Sen; Sha, Jing-Quan; Du, Bing; Tang, Bo
Abstract : A coupled hybrid of molybdenum phosphide and reduced graphene oxide has been synthesized utilizing Mo-based MOFs as precursors through a facile method for the first time. The nanocomposite exhibits superior electrocatalytic performance, which is one of the best MoP-based electrocatalysts under acidic conditions reported so far. Abstract : A coupled hybrid of molybdenum phosphide (MoP) and reduced graphene oxide has been prepared for the first time utilizing Mo-MOFs as precursors through a facile method. The nanocomposite exhibits superior electrocatalytic performance towards the HER, and is one of the best high-performance MoP-based electrocatalysts under acidic conditions reported so far.